2019
DOI: 10.1002/elan.201800880
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Chitosan Decorated Reduced Graphene Oxide‐Ferrocene Nanocomposite and its Application in Electrochemical Detection Rhodamine B

Abstract: Chitosan (CS) decorated reduced graphene oxide‐Ferrocene nanocomposite (RGO−Fc−CS) was synthesized by a one‐pot reaction. In the synthesis process of RGO−Fc−CS, GO−Fc was successfully self‐assembled via the π–π interaction, which had the features of large surface area and the high load. Then GO‐Fc and CS linked via one‐pot under alkaline conditions. The FT−IR, TGA, SEM were employed to characterize the successful synthesis of RGO−Fc−CS composites. A miniature electrochemical system was fabricated by RGO−Fc−CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…13 As a component of dyeing wastewater, RhB harms the ecological environment, too. 14 RhB can be found in industrial wastewater. Because RhB biodegradation is difficult, 15 it can damage plants and animals and pose a health threat to humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 As a component of dyeing wastewater, RhB harms the ecological environment, too. 14 RhB can be found in industrial wastewater. Because RhB biodegradation is difficult, 15 it can damage plants and animals and pose a health threat to humans.…”
Section: Introductionmentioning
confidence: 99%
“…4,10,11 Therefore, there is a need to develop a detection method that is high-speed, selective, reliable, and cost-effective. 4,14 In this regard, electrochemical analysis is a preferable option due to its simplicity, low cost, high sensitivity, good selectivity, low detection limit, fast detection, and real-time detection under in situ conditions. [32][33][34][35][36][37] The performance of electrochemical sensors is mainly determined by the electrocatalytic activity of the working electrode.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Yang and coworkers constructed an electrochemical sensor for polymer recognition and detection of Rhodamine B, using chitosan functionalized reduction of graphene oxide and ferrocene nanocomposites. 29 In the meantime, the results showed that the detection limit of the sensor could reach 0.5 nM.…”
mentioning
confidence: 95%